2009
DOI: 10.1186/1756-6606-2-28
|View full text |Cite
|
Sign up to set email alerts
|

A riot of rhythms: neuronal and glial circadian oscillators in the mediobasal hypothalamus

Abstract: Background: In mammals, the synchronized activity of cell autonomous clocks in the suprachiasmatic nuclei (SCN) enables this structure to function as the master circadian clock, coordinating daily rhythms in physiology and behavior. However, the dominance of this clock has been challenged by the observations that metabolic duress can over-ride SCN controlled rhythms, and that clock genes are expressed in many brain areas, including those implicated in the regulation of appetite and feeding. The recent developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
191
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(207 citation statements)
references
References 71 publications
14
191
0
Order By: Relevance
“…These findings are supported by work showing, respectively, that the Arc contains molecular clocks (1) that are reset in response to restricted meals (54) or fasting (32) and by the well-established finding that the SCN contains clocks that respond to photic cues. These results, therefore, add to the Arc's many roles an underappreciated functional circadian relationship with the SCN (60,68,78), as well as revealing an essential role for the Arc in maintaining circadian rhythms of ad libitum feeding independent of light entrainment.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…These findings are supported by work showing, respectively, that the Arc contains molecular clocks (1) that are reset in response to restricted meals (54) or fasting (32) and by the well-established finding that the SCN contains clocks that respond to photic cues. These results, therefore, add to the Arc's many roles an underappreciated functional circadian relationship with the SCN (60,68,78), as well as revealing an essential role for the Arc in maintaining circadian rhythms of ad libitum feeding independent of light entrainment.…”
Section: Discussionsupporting
confidence: 72%
“…Neurons exhibiting robust circadian rhythms that would be potentially capable of controlling circadian feeding rhythms are present in the Arc (1,32,37,54,81). Not only do Arc leptin receptors exhibit diurnal variation (25), but Arc LepR-B-expressing neurons receive and appear to integrate food-and energyrelated signals arising from diverse central and peripheral sites (9,17,45,88,95).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a large body of work has revealed that the mediobasal hypothalamic area (MBH), defined here as including the arcuate (Arc) and ventromedial nuclei, is a critical site for detection and integration of signals governing metabolism and feeding (6,27,29,75). Circadian oscillators capable of sustaining their rhythms ex vivo for up to 3 days have been demonstrated in the MBH (1,21). In some of these, the phase of the oscillation was altered by restricted feeding (21).…”
mentioning
confidence: 99%
“…Many recent studies have taken advantage of the mPER2::LUC fusion knock-in reporter mouse 4,5,9,19,25,[29][30][31]43 . This reporter system allows circadian phenotyping of cells and tissue explants including the SCN.…”
Section: Luciferase Reportersmentioning
confidence: 99%